Analisis Faktor-faktor yang Mempengaruhi Stress Primigravida Menghadapi Emesis Gravidarum - Merlin Karinda (Jurnal Kesehatan Indonesia, 2018)
The most influential response in pregnant women is nausea and vomiting. Primigravida pregnant women have a higher stress in the face of pregnancy. So it is necessary to do research to determine the direct and indirect influence and magnitude of information resources, the environment, the role of midwives and the role of husbands against the stress of primigravida mother face of morning sickness. The method used in this research the quantitative approach using cross-sectional design. The samples used were 80 primigravida mothers who experienced morning sickness as respondents. The analytical method used Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. The result findings that are stress primigravida pregnant woman influence of information source (10.39%), environment (28.60%), midwife role (18.30%) and husband's role (6.73%). The direct influence of mother's stress faced morning sickness by 64% and indirect effect of 0., 92% and total direct and indirect influence of 64.92%. the result of this research that the environmental variables the most affect the stress of primigravida mother facing morning sickness. It is because the environment of primigravida mother is very important role to stress levels of pregnant women especially primigravida especially social relations and phisical conditions of the house. Suggestion of research for prgnant women who experience morning sickness advised to always establish good relations with the whole family and neighbors so as to create a harmonious relationship.